If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -8) = 3(3x + -9) Reorder the terms: 6(-8 + 2x) = 3(3x + -9) (-8 * 6 + 2x * 6) = 3(3x + -9) (-48 + 12x) = 3(3x + -9) Reorder the terms: -48 + 12x = 3(-9 + 3x) -48 + 12x = (-9 * 3 + 3x * 3) -48 + 12x = (-27 + 9x) Solving -48 + 12x = -27 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -48 + 12x + -9x = -27 + 9x + -9x Combine like terms: 12x + -9x = 3x -48 + 3x = -27 + 9x + -9x Combine like terms: 9x + -9x = 0 -48 + 3x = -27 + 0 -48 + 3x = -27 Add '48' to each side of the equation. -48 + 48 + 3x = -27 + 48 Combine like terms: -48 + 48 = 0 0 + 3x = -27 + 48 3x = -27 + 48 Combine like terms: -27 + 48 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| -8(6m-6)-8m=440 | | x^2+7x+K=0 | | -(156x-13)= | | hg(x)=3.08(x)sqrt+18.97 | | 232=4(8n-6) | | 100=4(4-3x) | | -(156-13)= | | 95=5(4-3n) | | 2.28x-.8=2x+1.8 | | Hg(x)=3.08(52)sqrt+18.97 | | -5(-1-2p)+5p=95 | | .8x+.2=.6x+-10 | | 3x-7-x=5x+14 | | 6y-10=2+4y | | 5x-11=4x+7 | | -217=-6(-6v-6)-1 | | 6(7+3x)=150 | | 0=-5n-2m | | 18x+21=10x+90 | | -317=3+5(8k-8) | | 9y-3=4+2y | | X=3xj-4 | | 4x+7(1-5x)=-210 | | (-9,2)(-10,-4)= | | 4x^2+4x+9=0 | | 7m=5+8m | | 9t-14=-26+5t | | 3(k+2)=21 | | x^2-kx+3=0 | | x-0.8=8.29 | | 2u^2-3u+1=0 | | (2x-5)(3x-2)= |